Porosity of GEL-HA Composite Scaffolds Synthesized from Blue Swimming Crab Shells - Dionisius Advent Jiwa Pramana; Widi Widayat (Universitas Negeri Semarang, 2026)
Bone defects are a serious health problem requiring graft materials (scaffolds) with ideal porosity. This study aims todetermine the effect of varying gelatin concentrations on the porosity of hydroxyapatite-gelatin composites based on blueswimming crab shells. Blue swimming crab shells were utilized as an alternative source of hydroxyapatite (HA) becausethey are rich in calcium content and possess biocompatible characteristics. However, pure HA exhibits brittle mechanicalproperties, necessitating the addition of gelatin to bind the structure and reduce brittleness. The HA was processed usingthe microwave method. Scaffolds with varying gelatin concentrations of 2%, 3%, and 4% were fabricated using slurrycasting and oven drying methods. Characterization using X-Ray Diffraction (XRD) demonstrated that the HA synthesissuccessfully achieved a purity level of 99.6%. Porosity testing conducted using the liquid displacement method indicatedthat the pore percentage values ranged from 61.90% to 62.84%. The porosity trend exhibited a non-linear pattern, with thehighest porosity value achieved by the HAG-3 specimen at 62.84%. Based on the conducted research, the obtainedporosity values have met the minimum threshold for scaffolds, which is in the range of 50% to 90%.